Morphology of 9p21 homozygous deletion‐positive pleural mesothelioma cells analyzed using fluorescence in situ hybridization and virtual microscope system in effusion cytology. Issue 8 (28th February 2013) - Matsumoto, Shinji; Nabeshima, Kazuki; Kamei, Toshiaki; Hiroshima, Kenzo; Kawahara, Kunimitsu; Hata, Sakae; Marukawa, Katsuji; Matsuno, Yoshihiro; Taguchi, Kenichi; Tsujimura, Tohru
<x xml:space="preserve">Abstract</x> BACKGROUND In malignant pleural mesothelioma (MPM), most patients first present with pleural effusion; thus, cytologic analysis is the primary diagnostic approach. However, the cytologic distinction between MPM and reactive mesothelial cells (RMCs) in effusions can be extremely difficult due to the lack of both well‐established immunocytochemical markers and definite cytological criteria for MPM. Moreover, the existence of both MPM cells and RMCs in effusions from the same patient makes the differentiation even more challenging. Homozygous deletion of the 9p21 locus, the site of the cyclin‐dependent kinase inhibitor 2A/p16 (CDKN2A/p16) gene, frequently occurs in MPM but has never been reported in RMCs. The aim of this study was to define the cytomorphological characteristics of MPM cells, identified by the presence of 9p21 homozygous deletion by fluorescence in situ hybridization (FISH). METHODS For this purpose, cells on smear preparations were recorded using a virtual microscope system and were subjected to FISH analysis. Thereafter, 9p21 homozygous deletion‐positive cells were identified in the recorded virtual slides, followed by analysis of their morphological characteristics. RESULTS Mesothelioma cells positive for the 9p21 homozygous deletion exhibited significantly more frequent cell‐in‐cell engulfment, multinucleation (more than 2 nuclei), and larger multicellular clusters composed of more than 10 cells than did 9p21 deletion‐negative RMCs. Possible cutoff values are also proposed for these morphological markers to differentiate MPM cells from RMCs. CONCLUSIONS These morphological differences and cutoff values are useful for cytological differentiation of mesothelioma cells from RMCs. In addition, the novel technique of a combination of virtual microscopy and FISH is introduced for tumor morphological analysis. Cancer (Cancer Cytopathol) 2013;121:415–22. © 2013 American Cancer Society.